CORPUS LINGUISTIC APPROACHES TO ENGLISH SCIENTIFIC TERMINOLOGY - Zokirova Elinura Jasurovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article explores how corpus linguistic methods contribute to the analysis and understanding of English scientific terminology. It discusses the application of frequency analysis, concordance, collocation, and semantic prosody in identifying patterns and usage of scientific terms in authentic contexts. Drawing on corpora such as the British National Corpus (BNC), the Corpus of Contemporary American English (COCA), and specialized scientific subcorpora, the study demonstrates how data-driven approaches can reveal morphological, syntactic, and semantic features of terminological units. The paper concludes that corpus linguistics plays a crucial role in terminology management, translation, lexicography, and teaching English for Specific Purposes (ESP).